استخدام الهيدروجين كوقود لسيارات المستقبل وأثره الإيجابي على البيئة في سوريا - أسمر هيثم (Latakia University Journal -Engineering Sciences Series, 2019)
يزداد اهتمام العالم حالياً بالتحول إلى أنظمة تكنولوجية أكثر نظافة, يكون الهدف منها إنتاج حد أدنى من الغازات والملوثات, وكذلك إيجاد طاقة جديدة للمحروقات التي تلغي الحاجة إلى الوقود الأحفوري دون تدهور طبقة الأوزون. نحاول في بحثنا هذا أن نبين طريقة استخدام الهيدروجين كوقود للسيارات باعتباره غاز نظيف وغير سام وكذلك البحث في المعوقات الحالية التي تحد من استخدامه خاصة طرق التحميل والتخزين. بسبب التزايد المستمر في ملوثات عوادم السيارات في سوريا, كما في بقية دول العالم, فإن استخدام الهيدروجين يمكن أن يكون الحل الأمثل للحد منها, عند ذلك سوف تنخفض نسبة تلوث الهواء بحدود 60% من إجمالي الملوثات عامة. The world’s interest in conversion into cleaner technological systems is on the increase nowadays. The main purpose [of such systems] is to minimize the emission of gases and pollutants and finding new fuel energy that gets rid of demand for fossil fuel in order to stop the Ozone layer depletion. In this research, an attempt is being made to illustrate how to use Hydrogen as motorcar fuel, given that it is a clean and un-poisonous gas, and to examine the current obstacles which limit its use, particularly loading and storage methods. Due to constant increase in the pollutants released from motorcar exhaust-pipes in Syria, and in other world countries as well, the use of Hydrogen may be the ideal solution to reduce those pollutants. Thus, pollution rate in the air will drop by 60 % approximately out of the total pollutants.